Taxonomic contribution to the knowledge of Galumnidae (Acari, Oribatida, Galumnidae) from Cuba - Ermilov, Sergey G.; Kolesnikov, Vasiliy B.; Kontschán, Jenő; Klimov, Pavel B. (Zootaxa, 2023)
The present study is based on galumnid mites (Oribatida, Galumnidae) collected from leaf litter of two mixed forests in Cuba; six species from three genera are identified. Three new species—Pergalumna (Pergalumna) cienfuegosensis sp. nov., P. (P.) foveolatostriata sp. nov. and Galumna (G.) gigantea sp. nov.—are described. Allogalumna brevisetosa (Bayartogtokh & Weigmann, 2005) is recorded in the Neotropical region for the first time; P. (P.) obvia (Berlese, 1914) is recorded in Cuba for the first time.